Persistent organochlorine pollutants in liver of birds of different trophic levels from coastal areas of Campania, Italy - Naso B.; Perrone D.; Zaccaroni A.; Lucisano A.; FERRANTE, MARIA CARMELA (Archives of Environmental Contamination and Toxicology, 2003)
Liver samples of 12 species of birds of different trophic levels, collected during the period 1998-2000 from coastal areas of the Campania region, Southern Italy, were analyzed for organochlorine pesticides (OCs), such as dichlorodiphenyltrichloroethane (DDT) and its metabolites, hexachlorobenzene (HCB), gamma-hexachlorocycloexane (gamma-HCH), aldrin, dieldrin, endrin, and the seven PCB "target" congeners, IUPAC Nos. 28, 52, 101, 118, 138, 153 and 180. p,p'-DDE was present in all the samples analyzed, at concentrations ranging from 4 to 4504 ng/g wet wt, which were much higher than those found for HCB, dieldrin, and p,p'-DDD. The concentrations of the others OCs were below the detection limit in all the samples. PCBs were found in all the bird species at levels ranging between 6 and 8431 ng/g wet wt. The hepta-, hexa-, and penta-chlorinated congeners 180, 153, 138, and 118 were predominant since, in almost all the species, they contributed to more than 98% of the total seven determined PCBs. No significant differences in mean concentrations of organochlorine pesticides are detected between single species or between species grouped according to their feeding habits (p > 0.05). However, p,p'-DDE levels were higher in carnivorous species than in omnivorous and insectivorous ones (carnivorous > omnivorous > insectivorous). Concentrations of total PCBs were significantly higher in omnivorous birds than in carnivorous (p < 0.01) and insectivorous ones (p < 0.001), whereas carnivorous birds exhibited significantly higher total PCB levels than insectivorous ones (p < 0.01). Marked differences in total PCB concentrations were found also between single species (from p < 0.05 to p < 0.001). Levels of OCs and PCBs were generally below the thresholds known to affect reproduction, however, mean hepatic concentrations of total PCBs in the yellow-legged herring gull (Larus cachinnans), black-headed gull (Larus ridibundus), and kestrel (Falcus tinnunculus) were far higher than those estimated to elicit ...